2022
DOI: 10.1007/s40847-022-00199-9
|View full text |Cite
|
Sign up to set email alerts
|

Political stability and its effect on economy: some lessons from Sikkim Himalaya

Abstract: The Himalayan state of Sikkim has a unique political culture and social environment that could be replicated. Unlike other north-eastern states of India where ethnic identities have been intensely used for electoral politics and state developmentalism, the collective Sikkimese identity has taken precedence over narrow ethnic identity politics in Sikkim. As a result, the state has evolved as one of the most politically stable and better-governed states in India, resulting in rapid economic growth. This has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Regarding the effect of specific institutional factors, Singha and Singh (2022) confirm that political stability contributes to economic growth. Trabelsi and Trabelsi (2020) found that beyond the optimal threshold high and low corruption negatively impact economic growth.…”
Section: Reps 93mentioning
confidence: 74%
“…Regarding the effect of specific institutional factors, Singha and Singh (2022) confirm that political stability contributes to economic growth. Trabelsi and Trabelsi (2020) found that beyond the optimal threshold high and low corruption negatively impact economic growth.…”
Section: Reps 93mentioning
confidence: 74%